STOCK ANALYSIS USING NET CURRENT ASSET VALUE (NCAV) METHOD INDONESIA STOCK EXCHANGE 2015 ‒ 2020 - Vicky Aldo Linggarjati; Yuniningsih (Universitas Lambung Mangkurat, 2021)
Net Current Asset Value (NCAV) as a conservative method in value investing, can use to identify undervalued stock. Graham and Dodd introduce NCAV for the first time in their book “Security Analysis” (1934). The empirical study in US stock market prove that NCAV method can outperform market. The aim of this study to test NCAV method in Indonesia Stock Exchange period 2015-2020. This study compared the performance of NCAV portfolio to Indonesia Stock Exchange (IDX) Composite as the market index by average return using paired sample t-test. The performance of NCAV portfolio would divide by 3 holding period; 6 month, 12 month, and 18 month. The result of this study shows that NCAV portfolio tends to has bigger return than IDX Composite in all holding period, but not significant.